(untitled) (World Economics and Finance Bulletin, 2023)
The purpose of this research is to show the effect of oil price changes on foreign direct investment flows in Iraq using annual data during the period 2005-2020 . To achieve this research, and after reviewing the literature review in this domain, a ARDL model was used, after an application the unit root (ADF, PP) tests. The research concluded that changes in oil prices don’t affect the flows of foreign direct investment in Iraq during 2005-2020. Research recommended the necessity of providing an investment climate and political and economic stability to attract foreign direct investment .